Dory and the real true friend - Hanlon, Abby (Hanlon, Abby. Dory Fantasmagory., 2015)
Dory, a highly imaginative youngest child, makes a new friend at school but her brother and sister are sure Rosabelle is imaginary, just like all of Dory's other friends.